EFFORTS TO IMPROVE FUTSAL SHOOTING THROUGH GAME VARIATIONS - Sujarwo; Yusuf, Ramdan Muhammad; Setiakarnawijaya, Yasep (UNIVERSITAS NEGERI JAKARTA POSTGRADUATE OF PHYSICAL EDUCATION DEPARTMENTS, 2024)
This research is action research to improve shooting skills in futsal games in class V and VI students who are registered as futsal extracurricular participants at SDN Srengseng Sawah 04 with a total of 53 students as subjects. This action research uses the Kemmis Taggart model which consists of two cycles. The actions in this research use a variety of games to achieve the desired goals. Data was collected through observer observations in the form of movement truth tests, shooting tests, field notes, and documents during the research. The results of the research showed that after carrying out actions using game variations in cycle I, there were several students who were able to achieve a completeness score for the shooting movement correctness test (process) in cycle I, 22 (42%) students who were declared complete, and 31 (58%) students who were declared complete. %) others are declared incomplete. Then for the shooting accuracy test (product) cycle I, 34 (64%) students were declared complete and 19 (36%) were declared incomplete. From these results, there has been an increase, but as a group it is not more than or equal to 70% of the total number of students. Furthermore, in cycle II there was a significant increase. For students who were declared complete in the shooting movement correctness test (process), there were 53 (100%) students. Then for the shooting accuracy test (product) cycle II, 42 (79%) students were declared complete and 11 (21%) were declared incomplete. From the results of the movement correctness test and the second cycle shooting test, it was declared complete because as a group, the percentage of subjects who achieved the completeness criteria score was more than 70% of the total number of students, and it can be concluded that the application of game variations was able to improve the shooting of futsal extracurricular participants at SDN Srengseng Sawah 04. Keywords: Action Research, Game Variations, Shooting, Futsal